Analisis Wacana Kritis Terhadap Pemberitaan Isu Sampah di Media Rri.Co.Id - Iksander Iksander; Joko Mohamat Santoso (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
The issue of waste, as both an ecological and social problem, demands that mass media not only report facts but also frame a sense of collective responsibility between the government and society. This study analyzes how rri.co.id frames the issue of waste accumulation at the Temporary Disposal Site (TPS) in Bukit Betung, Bangka, using Norman Fairclough’s Critical Discourse Analysis framework. The analysis covers three dimensions: text, discourse practice, and social practice. At the textual level, rri.co.id employs a neutral and educational tone, using phrases such as “public awareness” and “shared responsibility.” The discourse practice dimension reveals a top–down communication pattern, with government officials as the dominant sources and citizens positioned merely as narrative support. In the social practice dimension, the reporting reinforces a paternalistic ideology, shifting responsibility primarily onto individual behavior while structural aspects—such as waste management policies and infrastructure—receive limited attention.